2009
DOI: 10.1038/oby.2009.4
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Heritability of Nonalcoholic Fatty Liver Disease in a Minority Cohort

Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with obesity and insulin resistance. The condition disproportionately affects Hispanic Americans. The aims of this study were to examine the risk factors and heritability of NAFLD in 795 Hispanic American and 347 African‐American adults participating in the Insulin Resistance Atherosclerosis Study (IRAS) Family Study. Computed tomography (CT) scans of the abdomen were evaluated centrally for measures of liver–spleen (LS) density ratio and abdominal fat dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 39 publications
6
82
1
Order By: Relevance
“…32 Compared to non-Hispanic whites, Hispanic individuals have significantly higher and non-Hispanic blacks have significantly lower prevalence of NAFLD. 15,[33][34][35] The prevalence of NAFLD in American-Indian and Alaskan-Native populations appears lower, ranging from 0.6% to 2.2%, although the lack of histologic definition makes it likely that is an underestimate. 36,37 There are data to suggest that hypothyroidism, hypopituitarism, hypogonadism, sleep apnea, and polycystic ovary syndrome independent of obesity are important risk factors for the presence of NAFLD (Table 4).…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…32 Compared to non-Hispanic whites, Hispanic individuals have significantly higher and non-Hispanic blacks have significantly lower prevalence of NAFLD. 15,[33][34][35] The prevalence of NAFLD in American-Indian and Alaskan-Native populations appears lower, ranging from 0.6% to 2.2%, although the lack of histologic definition makes it likely that is an underestimate. 36,37 There are data to suggest that hypothyroidism, hypopituitarism, hypogonadism, sleep apnea, and polycystic ovary syndrome independent of obesity are important risk factors for the presence of NAFLD (Table 4).…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…Although the prevalence of diabetes was similar in both groups (17%), metabolic syndrome was more common in Hispanics than African Americans (33% versus 19%), as was NAFLD (24% versus 10%). Liver density as determined by computed tomography scans was modestly heritable in both groups, estimated as 0.35 in Hispanics and 0.32 in African Americans ( 45 ).…”
Section: Heritability Of Hepatic Steatosismentioning
confidence: 99%
“…In view of the disproportionate incidence of NAFLD in Hispanics, Wagenknecht et al studied risk factors and heritability of NAFLD in the IRAS Family Study cohort, which included 795 Hispanic-American and 347 AfricanAmerican adults from large families recruited based on family size ( 45 ). The mean age of the cohort was 49 years, and 63% were female.…”
Section: Heritability Of Hepatic Steatosismentioning
confidence: 99%
“…7 Wagenknecht et al have reported that other markers for NAFLD are similar across ethnic groups and yet Hispanics do have the highest prevalence of NAFLD, hepatic steatosis, and elevated aminotransferase levels, followed by whites with the lowest rates in blacks. 29 Yet, at the same time, other markers such as triglycerides (TGs) and age are only associated with NAFLD in Hispanics. 29 It is possible that these apparent ethnic and familial differences are representative of an underlying genetic susceptibility.…”
Section: Ethnicity and Racementioning
confidence: 99%
“…29 Yet, at the same time, other markers such as triglycerides (TGs) and age are only associated with NAFLD in Hispanics. 29 It is possible that these apparent ethnic and familial differences are representative of an underlying genetic susceptibility. There are reports of familial clusters of NAFLD.…”
Section: Ethnicity and Racementioning
confidence: 99%